U.s.-mexico hydrodiplomacy: foundations, change, and future challenges - Margaret O. Wilder, Robert G. Varady, Stephen P. Mumme, Andrea K. Gerlak, Nicolás Pineda Pablos, Christopher A. Scott. (My University, 2019)
The year 2019 marked a significant milestone in U.S.-Mexico hydrodiplomacy: seventy-five years since the two countries adopted the Treaty of 1944, which apportioned between them the waters of the Rio Grande, Colorado River, and Tijuana River. Although the treaty is the countries&rsquo most notable and enduring act of hydrodiplomacy,[1] numerous cooperative agreements have followed over the past seven-plus decades. These arrangements have transformed transboundary water management in the region, in an arc away from conflict and toward greater cooperation and collaboration. Water scarcity along the U.S.-Mexico border has intensified due to various effects of climate change, economic development, population growth, and increasing water demand,[2] resulting in a complex array of water-governance challenges.[3] But paradoxically, transboundary binational institutions between the United States and Mexico have become more adept&mdashnot less so&mdashat devising innovative adaptations in water management. To some extent, this experience accords with study findings that show nations tend toward cooperation rather than conflict over water and that complexity need not be a deal breaker if water management institutions are robust.[4] This raises a crucial question to be addressed in this essay: how precisely have transboundary U.S.-Mexico relations evolved toward cooperation and collaboration?
Keywords: Hydrodiplomacy